(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
Sommario: PARTE I: LE INTERAZIONI CLASSICHE - 1. Salute e religione, un tema tradizionale in evoluzione - 2. La “religione” come cura. Santoni e guaritori - 3. Libertà religiosa versus tutela della salute. Le pratiche di mutilazione genitale femminile - 4. (segue) La circoncisione maschile - PARTE II: LE INTERAZIONI EMERGENTI - 5. Il dissenso religioso al trattamento sanitario. Il caso dei testimoni di Geova, e non solo - 6. Le nuove frontiere di tutela della salute nella legge n. 219 del 2017. Gli effetti sull’identità religiosa del paziente-fedele - 7. (segue) Gli spazi di obiezione di coscienza del personale medico sanitario. Religious identity and right to health. Classic and emerging interactions ABSTRACT: The relationship existing between health and religion is innate. Legal systems started dealing with it since the first formulations about freedom of religion and right to health, in order to take care of the individual and collective needs. Taking this premise into account, the first part of the essay analyzes the classic interactions between health and religion, in which the latter replaces official medicine or prescribes harmful conduct. Consequently, legal systems have developed resolutive dialectics which can be applied to new specific cases brought by multiculturalism, like infibulation. In the second part, the essay examines the emerging interactions caused by a third party - the medical health personnel - owner of the duty of care and freedom of conscience, recreating the solutions offered by doctrine and law. Lastly, it focuses on the objections which can be moved by the medical health personnel, which are connected to early end-of-life dispositions (law n. 219/2017), proposing solutions to the lack of regulation left by the law.